Religious anti-discrimination legislation and the negotiation of difference in Victoria, Australia. Issue 1 (1st January 2022) - Ezzy, Douglas; Banham, Rebecca; Beaman, Lori G.
ABSTRACT: This article examines the role of anti-discrimination legislation in the negotiation of religious difference in the Australian state of Victoria. We argue for the importance of a relational conceptualisation of the negotiation of religious diversity that draws on concepts of etiquette and limitations, deep equality, and substantive equality. The Victorian legislation allows the Victorian Civil and Administrative Tribunal (VCAT) to 'mediate' the relationships between the people and groups that come before it. VCAT mediates relationships in three ways: 1. Providing a forum for constructive intervention in cases of problematic tension between groups, and in doing so facilitating the development of an 'etiquette' for the negotiation of power dynamics, typically between (historically) empowered and disempowered groups in Australia. 2. Providing a forum for making transparent examples of latent and covert discrimination and exclusion, encouraging participants to engage in reflection upon potential future courses of action. 3. The provision (or refusal) of exemptions to the Equal Opportunity Act, providing guidance about the management of religious difference in the public sphere.